Food Delivery Business Plan - Abbasov, Javid (ADA University, 2022)
Considering the rapid expansion and volume of the food delivery industry, the business model of an online food delivery platform was picked as a startup idea. The main objective of this paper is to present a detailed business model of APPW, a mobile application that provides food delivery service to residents of Baku city, Azerbaijan. Regarding the methodology of the project, a quantitative and qualitative research approaches were applied in the process of market research. In order to achieve competitive advantage various strategic management techniques were utilized, including SWOT analysis, Porter’s Five Forces, Pestel analysis.
Keywords: Food delivery industry.; Online food delivery platform.; Business plan.; Business